2015
DOI: 10.1590/1519-6984.09113
|View full text |Cite
|
Sign up to set email alerts
|

How the fluctuations of water levels affect populations of invasive bivalve Corbicula fluminea (Müller, 1774) in a Neotropical reservoir?

Abstract: Corbicula fluminea is an invasive bivalve responsible for several environmental and financial problems around the globe. Despite the invasive potential of this species, it suffers certain restrictions in lentic environments due to natural phenomena that significantly affect its population structure (e.g. water column fluctuation and sunlight exposure). The present study addresses how temporal decline of the water level in a Neotropical reservoir and exposure to sunlight affect the population structure of C. fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
8
1
3
Order By: Relevance
“…As the maturation of snails was anticipated (approximately 0.41 years, 13.20 mm) the species is already able to reproduce at reduced sizes, being capable of structure itself faster in the environment than native species. Invasive species may, thus, displace native species, due to the characteristics cited above (Paschoal et al, 2015). The high proportion of adults in the study area was also observed in other reservoirs of Brazil (Suriani et al, 2007;Santos & Eskinazi-Sant'Anna, 2010), highlighting the ecological risks that this species can play in environments.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…As the maturation of snails was anticipated (approximately 0.41 years, 13.20 mm) the species is already able to reproduce at reduced sizes, being capable of structure itself faster in the environment than native species. Invasive species may, thus, displace native species, due to the characteristics cited above (Paschoal et al, 2015). The high proportion of adults in the study area was also observed in other reservoirs of Brazil (Suriani et al, 2007;Santos & Eskinazi-Sant'Anna, 2010), highlighting the ecological risks that this species can play in environments.…”
Section: Discussionmentioning
confidence: 52%
“…The population of M. tuberculata was well established at the Cachoeira II reservoir, semi-arid Pernambuco state (Northeast Brazil). This was not a good news, once this invasive species is capable of repel native species, modify aquatic habitats and alter environment scenario (Santos et al, 2012), such as other invasive species: C. fluminea (Paschoal et al, 2015) and L. fortunei (Darrigran & Damborenea, 2006;Darrigran et al, 2007).This result could be related both to the environment aspects, since the species tolerates different substrates (having more affinity to the soft bottom substrate with the macrophytes presence), as well as to the biology of the species, characterized by rapid growth, early maturation and population composed mainly by adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population of C. fluminea in the late 1980's was increasing, right after its introduction into Río de la Plata River, but now, 25 years later, the population is in lower densities and individuals are on average smaller (less than 20 mm length), indicating that the population is shrinking. It is possible that a decrease in population density could be caused by environmental changes such as extreme variations in the water level (Paschoal et al 2015). However, such changes are temporal and the population usually recovers when conditions are reversed.…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater ecosystems are especially vulnerable as a result of widespread human disturbance (Havel et al 2005;Turak et al 2016). Invasive bivalves are among the most successful invasive species in freshwater ecosystems (Ricciardi 2007;Oliveira et al 2011;Paschoal et al 2015;Ng et al 2018), which typically comprise r-selected species which adapt to colonize a wide range of aquatic environments and exhibit high fecundity, rapid growth, and broad physiological tolerance to several abiotic factors (Hayes et al 2015;Nakano et al 2015). Such characteristics allow them to become dominant species (Karatayev et al 2007).…”
Section: Introductionmentioning
confidence: 99%